Comic Media Development Remaining World War II Historical Site in Ambon Island - Matitaputty, Jenny Koce; Pattiasina, Johan; Sopacua, Jems (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The purpose of this study was to develop appropriate comic learning media for Ambon Island historical heritage sites for students of the History Education Study Program at Pattimura University. To answer the existing problems, the researcher uses the Research and Development method using the ADDIE research model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data analysis technique was carried out descriptively and the data questionnaire was calculated qualitatively for expert validation and quantitatively for testing student respondents in history education study programs. The results showed that the validation results from learning material experts obtained a score of 40 and the percentage was 90%. The validation results from learning media experts obtained a score of 92 with a percentage of 96.8%. The validation results from linguists obtained a score of 31 and the percentage was 88.6%. Meanwhile, for student responses to learning media, a pretest test was carried out on 25 students of the history education study program which was 38.4 while the posttest score was 95.12.